BRAND SEBAGAI KEKUATAN PERUSAHAAN DALAM PERSAINGAN GLOBAL - Yussy Santoso; Ronnie Resdianto (Business Management Journal, 2007)
AbstrakMany industries grow fast before and after globalization. In this period, the company must think about production, financing, operation, human resource management, and marketing. It is important to market their products or services unto customers. Marketing mix includes product, price, place, and promotion. One aspect of product mix is brand. Brand is one aspect for company strength in global competitiveness. In this time, brand explains about : Positioning-Differentiate-Brand Theory, Brand Communication, Brand Equity, Strategy Brand Management.Kata KunciBrand, Global Competitiveness, Brand Communication, Brand Equity